2012
DOI: 10.1523/jneurosci.1596-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Population Response to Natural Images in the Primary Visual Cortex Encodes Local Stimulus Attributes and Perceptual Processing

Abstract: The primary visual cortex (V1) is extensively studied with a large repertoire of stimuli, yet little is known about its encoding of natural images. Using voltage-sensitive dye imaging in behaving monkeys, we measured neural population response evoked in V1 by natural images presented during a face/scramble discrimination task. The population response showed two distinct phases of activity: an early phase that was spread over most of the imaged area, and a late phase that was spatially confined. To study the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 67 publications
3
21
0
Order By: Relevance
“…We showed that the latency to peak response at the center of achromatic surfaces increased with distance from the edges and that the responses seemed to propagate linearly from the edges to the center. The mean propagation speed of the population response was well within the range of previously reported horizontal connections' speed (Grinvald et al, 1994;Bringuier et al, 1999;Slovin et al, 2002). Our findings therefore support a horizontal-connection-mediated neuronal filling-in mechanism for achromatic surfaces (Spillmann and De Weerd, 2003;Huang and Paradiso, 2008).…”
Section: Achromatic Squares Late Increase Of Center Responses May Be supporting
confidence: 86%
See 2 more Smart Citations
“…We showed that the latency to peak response at the center of achromatic surfaces increased with distance from the edges and that the responses seemed to propagate linearly from the edges to the center. The mean propagation speed of the population response was well within the range of previously reported horizontal connections' speed (Grinvald et al, 1994;Bringuier et al, 1999;Slovin et al, 2002). Our findings therefore support a horizontal-connection-mediated neuronal filling-in mechanism for achromatic surfaces (Spillmann and De Weerd, 2003;Huang and Paradiso, 2008).…”
Section: Achromatic Squares Late Increase Of Center Responses May Be supporting
confidence: 86%
“…The average speed was 0.088 Ϯ 0.0045 m/s. This speed is in the range of the previously reported horizontal connections speed (Grinvald et al, 1994;Bringuier et al, 1999;Slovin et al, 2002). The derived velocities were reproducible across different square sizes and spatial profiles (see Materials and Methods).…”
Section: Achromatic Square Responses Increase Slower As a Function Ofsupporting
confidence: 78%
See 1 more Smart Citation
“…Recently visual image encoding was studied using VSDi in behaving monkeys by recording the population response evoked in V1 by the presentation of the natural images during a face/scramble discrimination task. 96 Authors reported that the population response showed two phases: (1), that was spread over most of the area of the recording, and (2), which was spatially confined. 96 These experiment results present a spatial encoding of low-and high-level features of visual images in the V1: the low level is correlated to the image's basic local attributes and the high level is related with the perceptual outcome of the visual image processing.…”
Section: Vsdi In Neurosciencementioning
confidence: 99%
“…96 Authors reported that the population response showed two phases: (1), that was spread over most of the area of the recording, and (2), which was spatially confined. 96 These experiment results present a spatial encoding of low-and high-level features of visual images in the V1: the low level is correlated to the image's basic local attributes and the high level is related with the perceptual outcome of the visual image processing. 96 Neural responses in response to collinear or orthogonal arrays of Gabor patches have been visualized by the VSDi imaging in the awake monkey.…”
Section: Vsdi In Neurosciencementioning
confidence: 99%